Safety and health in ports. (International Labour Office., 2005)
This essential code of practice, intended to replace both the second edition of the ILO Code of Practice on Safety and Health in Dock Work (1977) and the ILO Guide to Safety and Health in Dock Work (1976), provides valuable advice and assistance to all those charged with the management, operation, maintenance and development of ports and their safety.